2009
DOI: 10.1210/en.2009-0700
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Amplify Dibutyl Phthalate-Induced Disruption of Testosterone Production and Male Reproductive Development

Abstract: Common male reproductive abnormalities including cryptorchidism, hypospadias, and low sperm counts may comprise a testicular dysgenesis syndrome (TDS), resulting from fetal testis dysfunction during a critical developmental period involving reduced androgen production/action. The recent increase in TDS prevalence suggests environmental/lifestyle factors may be etiologically important. The developing fetus is exposed to multimodal challenges, and we hypothesized that exposure to a combination of factors rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 70 publications
5
70
0
1
Order By: Relevance
“…There is also evidence from human (13,14) and animal experimental (15) studies that fetal programming can influence adult testosterone levels, particularly that reduced fetal androgen exposure leads to lower adult male testosterone levels (14,15). This data fits with growing evidence that subtle deficiency in fetal androgens is a major determinant of adult male reproductive disorders, such as low sperm production (16,17), and might explain why low sperm counts are often associated with compensated Leydig cell failure in men (18).…”
supporting
confidence: 67%
See 1 more Smart Citation
“…There is also evidence from human (13,14) and animal experimental (15) studies that fetal programming can influence adult testosterone levels, particularly that reduced fetal androgen exposure leads to lower adult male testosterone levels (14,15). This data fits with growing evidence that subtle deficiency in fetal androgens is a major determinant of adult male reproductive disorders, such as low sperm production (16,17), and might explain why low sperm counts are often associated with compensated Leydig cell failure in men (18).…”
supporting
confidence: 67%
“…There is a similar connection between reduced fetal androgens and reduced adult sperm counts/sperm production in men and rats (15,16). What further ties these observations together is that men with low sperm counts commonly exhibit compensated adult Leydig cell failure, although why is unknown (18,60,67).…”
Section: -Hsd3mentioning
confidence: 87%
“…In addition, exposure to dexamethasone exacerbated 500 mg/kg DBP-mediated reduction in adult testicular weight and resulted in reduced testicular weight when given in combination with 100 mg DBP, compared with controls. Overall, these effects paralleled the reductions in plasma testosterone levels of DBP treated rats (Drake et al, 2009). Furthermore, immature male rat treated daily with di-(2 ethylhexyl) phthalate (DEHP) and flutamide (Flu) on postnatal days (PNDs) 21 to 35 showed significant decreases in the weights of the testes, prostate, and seminal vesicle and anogenital distances (AGD) in response to high DEHP dose (500 mg/kg body mass) or Flu (50 mg/ kg body mass) (Vo et al, 2009).…”
Section: Effects On Steroidogenic Enzyme Genesmentioning
confidence: 68%
“…Otherwise, our observation is in accordance with the of study of Brunström et al (2009), showing that plasma testosterone concentration was not affected when Quail embryos were exposed to EDCs, suggesting that the observed impeded growth was not due to insufficient testosterone levels. Elsewhere, it was reported that fetal exposure of rats to DBP at 100 mg/kg or dexamethasone (0.1 mg/kg) alone had no effects on testis weight, ventral prostate weight, or penis length, whereas 500 mg DBP/kg significantly reduced these parameters (Drake et al, 2009). In addition, exposure to dexamethasone exacerbated 500 mg/kg DBP-mediated reduction in adult testicular weight and resulted in reduced testicular weight when given in combination with 100 mg DBP, compared with controls.…”
Section: Effects On Steroidogenic Enzyme Genesmentioning
confidence: 99%
“…The MPW refers to the window of time during fetal development in which androgen actions program later development of all male reproductive organs, including their ultimate adult size and function (20)(21)(22). A vital finding was that anogenital distance (AGD), which is normally about twice as long in rodent males as in females, was also programmed by androgen action within the MPW (20,23).…”
Section: Introductionmentioning
confidence: 99%